2018
DOI: 10.7567/jjap.57.021304
|View full text |Cite
|
Sign up to set email alerts
|

Effect of low-oxygen-concentration layer on iron gettering capability of carbon-cluster ion-implanted Si wafer for CMOS image sensors

Abstract: The effect of oxygen (O) concentration on the Fe gettering capability in a carbon-cluster (C 3 H 5 ) ion-implanted region was investigated by comparing a Czochralski (CZ)-grown silicon substrate and an epitaxial growth layer. A high Fe gettering efficiency in a carbon-cluster ion-implanted epitaxial growth layer, which has a low oxygen region, was observed by deep-level transient spectroscopy (DLTS) and secondary ion mass spectroscopy (SIMS). It was demonstrated that the amount of gettered Fe in the epitaxial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 35 publications
(60 reference statements)
1
22
0
Order By: Relevance
“…Third, the passivation effect on interface state defects at the SiO 2 /Si interface is expected owing to the hydrogen of hydrocarbon molecular ions trapped in the projection range and diffusing during device thermal processes . Previous studies indicated the gettering capability of these novel silicon epitaxial wafers for metal impurities and the oxygen diffusing from bulk silicon . Furthermore, Yamaguchi demonstrated that these novel silicon epitaxial wafers reduce the dark current due to the interface state defects at the SiO 2 /Si interface.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Third, the passivation effect on interface state defects at the SiO 2 /Si interface is expected owing to the hydrogen of hydrocarbon molecular ions trapped in the projection range and diffusing during device thermal processes . Previous studies indicated the gettering capability of these novel silicon epitaxial wafers for metal impurities and the oxygen diffusing from bulk silicon . Furthermore, Yamaguchi demonstrated that these novel silicon epitaxial wafers reduce the dark current due to the interface state defects at the SiO 2 /Si interface.…”
Section: Introductionmentioning
confidence: 99%
“…These novel silicon epitaxial wafers have three characteristics that can solve the above technical issues leading to the development of advanced CMOS image sensors. First, the projection range of a hydrocarbon molecular ion has a high gettering capability for metallic impurities . Second, the projection range of a hydrocarbon molecular ion also has a barrier effect on oxygen impurities .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, we have recently demonstrated that hydrocarbon-molecular-ion implantation in an epitaxial growth layer with a low O concentration, rather than in the CZ-Si substrate, resulted in a higher gettering capability for intentionally contaminated Fe [ 22 ]. It was found that the gettering capability for Fe is determined by the O concentration in the hydrocarbon-molecular-ion implantation region.…”
Section: Introductionmentioning
confidence: 99%